Modeling economic growth in contemporary Belarus - Sergi, Bruno S. (Entrepreneurship and global economic growth, 2019)
Since 1991, the eyes of the world have been on the economic growth and development of the states that formerly made up the Soviet Union. Looking at Belarus's industrial structure, economic growth, and economic prospects, this edited collection analyses why Belarus is considered ahead of many of its neighbour states in terms of human development. Looking across both medium- and long-term economic growth, editor Bruno S. Sergi brings together a cast of expert contributors to analyse the foreign and domestic policies that affect Belarus's economy. Across the 20 chapters included in the book, the contributors explore the largest industries in Belarus, including the financial, technology, tourism, and energy industries. With chapters on foreign investments, exports and imports, and regional policy, this is a text that looks across the whole breadth of the economy. Finally, the contributors suggest factors to increase the growth of Belarus's economy, such as launching smart cities, expanding logistic services and the tourism and hospitality industry, and the modernization of the agrarian sector.For students and researchers in political economy, or international economics, this is a vital text exploring an important, but underrepresented, economy.